QUIET QUITTING: REFLEKSI TEOLOGI KERJA DALAM PERSPEKTIF IMAN KRISTEN - Waruwu, Tommi Ferdinan; Romika; Tju Lie Lie (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2025)
Quiet quitting has become a concern in the modern workplace because it reflects an imbalance between work demands and individual well-being. This phenomenon impacts work motivation, organizational culture, and company productivity. This study aims to analyze this phenomenon from the perspective of Christian theology of work, by examining the causal factors, impacts, and ethical solutions offered by the principles of faith. Using a qualitative method with a phenomenological approach, this study collected data through interviews, surveys, and literature studies of theologians such as Gregori Guitian and Scott Paeth. The results of the study show that although the Bible emphasizes hard work and responsibility, Christian values ​​also teach balance in life, social justice, and respect for the dignity of workers. Quiet quitting does not always conflict with the principles of faith if it is understood as a form of resistance to exploitative work systems and as an effort to maintain mental health. Therefore, the integration of the theology of work into organizational culture is needed to create a fairer work environment, support employee well-being, and build open communication and proper appreciation. In conclusion, work in the Christian faith is a form of worship and service that must be carried out with integrity, dedication, and balance. By applying the principles of the theology of work, organizations can overcome this phenomenon and create a more positive, productive, and meaningful work culture for each individual.